Serum 25-hydroxyvitamin D concentrations are inversely associated with body adiposity measurements but the association with bone mass is non-linear in postmenopausal women - Vijay Ganji (8710491) (2021)
Vitamin D deficiency has been linked to increased adiposity and decreased bone density. It is not known if vitamin D is linked to adiposity measures and bone mass in postmenopausal Qatar women. We investigated an association between serum vitamin D [25-hydroxyvitmain D (25(OH)D)] and adiposity measurements in postmenopausal women using Qatar Biobank data (n = 935). The post-menopausal status was self-reported by participants. Multivariate adjusted regression was applied to determine the association between serum 25(OH)D and body adiposity markers and bone mass. Serum 25(OH)D was significantly, inversely associated with body mass index (p < 0.0005), waist circumference (0.044), fat mass (p < 0.003), gynoid fat (p < 0.001), and android fat (p < 0.009). Serum 25(OH)D appeared to have an inverse ‘U’ association with several adiposity measures. Overall, body adiposity markers were the lowest in the 4th quartile serum 25(OH)D and significantly lower compared to the 1st quartile serum 25(OH)D. In multivariable adjusted analysis, no association was found between serum 25(OH)D concentration and bone mass when serum 25(OH)D was categorized. In a continuous variable analysis, the association between 25(OH)D and bone mass was significant, non-linear, inverse ‘U’. In conclusion, serum 25-hydroxyvitamin D was inversely associated with adiposity measures and non-linearly associated to bone mass in postmenopausal Qatari women. Other Information Published in: The Journal of Steroid Biochemistry and Molecular Biology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jsbmb.2021.105923